The Potential Role of Exosomal Proteins in Prostate Cancer - Feng, Shangzhi; Lou, Kecheng; Zou, Xiaofeng; Zou, Junrong; Zhang, Guoxi (Frontiers in Oncology, 2022)
Prostate cancer is the most prevalent malignant tumor in men across developed countries. Traditional diagnostic and therapeutic methods for this tumor have become increasingly difficult to adapt to today’s medical philosophy, thus compromising early detection, diagnosis, and treatment. Prospecting for new diagnostic markers and therapeutic targets has become a hot topic in today’s research. Notably, exosomes, small vesicles characterized by a phospholipid bilayer structure released by cells that is capable of delivering different types of cargo that target specific cells to regulate biological properties, have been extensively studied. Exosomes composition, coupled with their interactions with cells make them multifaceted regulators in cancer development. Numerous studies have described the role of prostate cancer-derived exosomal proteins in diagnosis and treatment of prostate cancer. However, so far, there is no relevant literature to systematically summarize its role in tumors, which brings obstacles to the later research of related proteins. In this review, we summarize exosomal proteins derived from prostate cancer from different sources and summarize their roles in tumor development and drug resistance.